From Youth Bulge to Ageing Society: Dependency Ratio, Life Expectancy and Disability among Older Adults in Nepal (1991–2021) - Sharma, Tilak Prasad; Shakya, Dhanendra Veer (KMC Journal, 2026)
Nepal is witnessing a very fast demographic transition of the young to the aging society with dire consequences in the social, health and development policies. The article is intended to be a review of population composition, dependency ratio, and survival rates. The National Population and Housing Census (NPHC) was used to calculate life expectancy and disability rates among older individuals (60 and older) in Nepal from 1991 to 2021. The results indicate that the percentage of children (0-14 years) has been on the decline since 1991, varying between 42.4% and 27.8% as at 2021. At the same time, there is an increase in the population of working-age (15-59 years) and older people (5.8% to 10.2%). There are regional and gender-based differences as well: the greatest life expectancy in age until 60 is found in hilly regions and among women, whereas the expected lifespan at the age of 60 differs across provinces, with a higher expectancy in the Mountain and Sudurpashchim regions. Disability in the aged is estimated at 6.9 percent, with the most common impairments being physical, visual and auditory impairments. The provincial and ecological disparities predict that aging in Nepal is heterogeneous, and context-specific policies are needed. The findings highlight the importance of leveraging the demographic dividend, improving health and long-term care systems, and implementing inclusive social protection and age-friendly policies. The paper presents evidence of a nationally representative and sub-nationally disaggregated study that can be used to shape the approach to healthy aging and proactive planning to guarantee longer, healthier, more autonomous, and dignified lives.